RELATIVISTIC STELLAR CLUSTERS - Merafina, Marco (Одеські астрономічні публікації, 2017)
Star clusters with very high densities may play an important role in QSO and nuclei of galaxies. This role is strongly influenced by relativistic instability which can be reached at different critical densities under particular conditions (e.g. the formation of massive black holes in AGN’s). On the other hand it exists the possibility to have stable relativistic clusters with arbitrarily large central redshift (and density). The equilibrium and stability of relativistic clusters described by a Maxwellian distribution function with a cutoff in phase space is discussed. The results are compared and contrasted with ones existing in literature.